COMPLEX PERFORMANCE ANALYSIS IN BALL SPORTS - Kovács, Miklós; Balogh, László; Pöszmet, Tibor; Pucsok, József Márton (Stadium - Hungarian Journal of Sport Sciences, 2022)
Assessing athletes’ capabilities has never been as widespread as it is nowadays. Several methods have evolved and developed in recent decades to measure physical or mental skills accurately. However, these assessment protocols became more and more specific. They focused on a certain attribute, as if we forget that athletes’ game performance is not equal to the total of different skills. Since psychomotor skills interact during games, test protocols should be similar and measured comprehensively. Two groups of ball sport players, thirteen soccer players (n=13) and ten handball players (n=10), have been tested on the SpeedCourt training system to find a relationship between the results of two tests (Micromovement Test, MT) and traditional indicators, such as Heart Rate Recovery (HRR), Body Mass Index (BMI) and Body Fat Percentage (BFP). Furthermore, the correlation in performances of the two groups has also been analyzed. We found no significant correlation between the two MT and HRR results (r=0,5132 and r=-0,5588). Similarly, there are significant correlation neither MT and BMI (r=-0.0886 and r=-0.0174) nor MT and BFP results (r=0.0872 and r=-0,2399). A significant difference cannot be found between the MT results of the two groups that indicate that MT applicable for both sports.